The Influence of Political Dynamics on Health Policy in Indonesia - Nasution, Irfan Sazali; Zuhra, Fatimah; Fatiha, Alifa; Putri, Syfa Ardhia; Felisha, Ravena; Br Sembiring, Wira Anjani; Hasibuan, Wulan; Syaputri, Marsha Aulia; Sabrina, Zakiatus; Larasati, Yulfani (Universitas Ibn Khaldun Bogor, 2024)
Health policy in Indonesia has experienced various significant changes in line with the political dynamics that occur at the national and local levels. Political dynamics in Indonesia are greatly influenced by various factors, such as the government system, political party ideology, interests of certain groups, and issues that develop in society. This study aims to analyze the influence of political dynamics on health policy in Indonesia, focusing on the post-reform period. The research methodology uses the literature review study method to analyze the influence of political dynamics on health policy in Indonesia. Literature review study is an effective method to collect, analyze, and synthesize information from various sources relevant to the research topic. The summary of the results of the discussion highlights the significant impact of political dynamics on health policy in Indonesia. The discussion emphasized the challenges faced due to changes in political leadership and decentralization of policy coordination. The role of political ideology, collaboration between stakeholders, and global influence in shaping health policies is essential for effective and sustainable health in Indonesia. By understanding the political dynamics that affect health policy, it is hoped that the recommendations produced from this study can make a significant contribution to future health policy improvements in Indonesia.